Avaliação da Ação do Peptídeo Antimicrobiano Dermadistinctina K em Membrana Modelo por Dinâmica Molecular - Moema Monteiro Batista (2015)
A vast diversity of plants and animals has peptides in their innate immune system. These molecules modulate the nervous, immune and circulatory system of predators, which are of great interest to the pharmaceutical industry concerning the discovery of new active biomolecules. The resistance to antimicrobial agentes becomes prevalent, drugs turn out be less effective against bacteria, fungi, protozoans and viruses, new pharmaceutical compounds are necessary to deal with this widespread phenomenon. The subject of study in this work is an antimicrobial peptide with potential antibiotic activity and whose action mechanism remains mostly unknown. This peptide, Dermadistinctin K (DD K) is found on the skin of the anuran Phyllomedusa distincta from the Brazilian Atlantic Forest. This study focused on the interaction of the peptide DD K with a membrane model of 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocoline (POPC) with the aim to collect information in silico to elucidate its action and support the development of antimicrobial drugs. This thesis has in three parts. On part one; we conducted a study of structural prediction of the DD K peptide in trifuorethanol/water mixture (TFE/water) (50%/50%, v/v), employing Generalized Simulated Annealing (GSA) using Thor-GSA software, developed in our research group, and Molecular Dynamics (MD) simulation using GROMACS 4.6. The GSA has made possible to find a pre-folded structure for DD K, which in sequence was submitted to MD simulation and finished folded in the native structure, an amphipathic helix. On part two we determined systems with 2,3 and 4 peptides in bilayer with 512 molecules of POPC. Membrane model modifications were observed as also misfolded aggregates of DD K. DD K monomers aggregates by hydrophobic face of each helix of peptide. Hydrophilic face of DD K is formed mainly by lysine amino acid residues that interacted with headgroups of membrane. On the final part we used pre-mounted pores with 6 peptides/468 lipids, 7 peptides/ 461 lipids and 8 peptides/454 lipids of POPC bilayer. Two pore configurations were used: one with the lysine residues turned to outside of pore, and another with these residues turned inwards and making up the pore lumen. There were water passage, bilayer pertubation and pore stabilization in both models. The pores with 6 and 7 peptides formed stable but collapsed structures,while lysine residues dragged headgroup of phospholipids into the bilayer forming intertices giving passage of water molecules. Pores with 8 peptides stabilized with the charged positive residues into the center preveting the pore colapse by electrostatic repulsion and forming a lumen through which water molecules can pass. In conclusion, when the peptide critical concentration to aggregate is reached to osmotic leaking can occur through several mechanisms at once. These mechanism include the disturbance of the bilayer by aggregates of peptide, the formation of pores by fusion of hydrophobic phases, that could be happen on up to 7 peptides, and the formation of barrel pores could be suggested by the orderly aggregation of up 7 peptides forming a lumen.